‘Candidatus Liberibacter asiaticus’ Multimeric LotP Mediates Citrus sinensis Defense Response Activation - Merli, Marcelo L.; Padgett-Pagliai, Kaylie A.; Cuaycal, Alexandra E.; Garcia, Lucila; Marano, Maria Rosa; Lorca, Graciela L.; Gonzalez, Claudio F. (Frontiers in Microbiology, 2021)
'Candidatus Liberibacter asiaticus’ is known as the most pathogenic organism associated with citrus greening disease. Since its publicized emergence in Florida in 2005, ‘Ca. L. asiaticus’ remains unculturable. Currently, a limited number of potential disease effectors have been identified through in silico analysis. Therefore, these potential effectors remain poorly characterized and do not fully explain the complexity of symptoms observed in citrus trees infected by ‘Ca. L. asiaticus’. LotP has been identified as a potential effector and have been partially characterized. This protein retains structural homology to the substrate binding domain of the Lon protease. LotP interacts with chaperones like GroEL, Hsp40, DnaJ, and ClpX and may exercise its biological role through interactions with different proteins involved in proteostasis networks. Here, we evaluate the interactome of LotP - revealing a new protein-protein interaction target (Lon-serine protease) and its effect on citrus plant tissue integrity. We found that via protein-protein interactions LotP can enhance Lon protease activity, increasing the degradation rate of its specific targets. Infiltration of purified LotP strained citrus plant tissue causing photoinhibition and chlorosis after several days. Proteomics analysis of LotP tissues recovering after the infiltration revealed a large abundance of plant proteins associated with the stabilization and processing of mRNA transcripts, a subset of important transcription factors, and pathways associated to innate plant defense were highly expressed. Furthermore, LotP’s interactions and substrate binding module suggest potential interactions with plant proteins, most likely proteases.